Styles of academic production in the Argentine social sciences: Heterogeneity and heterodoxy - Piovani, Juan Ignacio (2020)
Argentina is an appealing case for analyzing the social science system. In recent years (until 2015) there has been a robust increase in public funding, giving way to the expansion of research, the recruitment of hundreds of new full-time researchers and the consolidation of scholarships for PhD students. All this, in turn, has resulted in a remarkable increase in publications. Although these processes have occurred in the midst of professionalization (which implies higher levels of adherence to international academic standards), recent studies have shown that two contesting models within the social sciences continue to prevail in Argentina: one that conforms to international standards and practices, and another of a more endogenous nature, with its own logic for knowledge production, evaluation and circulation. In order to examine the impact of international standards in the Argentine social sciences, in this paper I analyze the styles of academic production. This implies the study of three closely related dimensions: research processes and models (theoretical foundations, methods, techniques, etc.); writing formats (structure and organization of academic texts); and publication logics (types of publications, profiles of the journals where the articles are published, etc.). The analysis is based on a large sample of publications selected by other researchers in order to carry out a comprehensive review of Argentine literature with regard to six key themes of the social sciences. These publications were also used to produce a dataset with several variables related to the three above-mentioned dimensions. In particular, this paper focuses on the publications grounded in empirical research, and compares qualitative with quantitative research and the various types of publications (journal articles, book chapters and conference papers). The results show that regardless of the recent process of professionalization, “heterodox models” of academic production are still largely pervasive within the Argentine social sciences.